A New Microfluidic Device for Classification of Microalgae Cells Based on Simultaneous Analysis of Chlorophyll Fluorescence, Side Light Scattering, Resistance Pulse Sensing - Junsheng Wang (Micromachines, 2016)
Fast on-site monitoring of foreign microalgae species carried by ship ballast water has drawn more and more attention. In this paper, we presented a new method and a compact device of classification of microalgae cells by simultaneous detection of three kinds of signals of single microalgae cells in a disposable microfluidic chip. The microfluidic classification device has advantages of fast detection, low cost, and portability. The species of a single microalgae cell can be identified by simultaneous detection of three signals of chlorophyll fluorescence (CF), side light scattering (SLS), and resistance pulse sensing (RPS) of the microalgae cell. These three signals represent the different characteristics of a microalgae cell. A compact device was designed to detect these three signals of a microalgae cell simultaneously. In order to demonstrate the performance of the developed system, the comparison experiments of the mixed samples of three different species of microalgae cells between the developed system and a commercial flow cytometer were conducted. The results show that three kinds of microalgae cells can be distinguished clearly by our developed system and the commercial flow cytometer and both results have good agreement.